Ambivalent encounters : childhood, tourism, and social change in Banaras, India - Huberman, Jennifer (Rutgers series in childhood studies., 2012)
This ethnographic study brings together scholarship on the anthropology of childhood, tourism, consumption, and exchange to examine how and why children working as unlicensed peddlers and tourist guides along the waterfront of Banaras, India, a popular and iconic tourist destination, elicit such powerful reactions from western visitors and locals in their community and explores how the children themselves experience their work and render it meaningful. Ambivalent Encounters brings together scholarship on the anthropology of childhood, tourism, consumption, and exchange to ask why children emerge as objects of the international tourist gaze; what role they play in representing socio-economic change; how children are valued and devalued; why they elicit anxieties, fantasies, and debates; and what these tourist encounters teach us more generally about the nature of human interaction.